3 Building effective stroke systems of care through a regional emergency medical services (EMS) coalition and data transparency initiative: the south florida experience. (25th July 2019) - Mehta, B; Antevy, P; Katz, R; Sessa, J; Scheppke, K; Pepe, P; Hanel, R; Mokin, M; Gutierrez, C; Romano, J; Nogueira, R; Jadhav, A; et al.
Abstract : Introduction: Advances in acute stroke treatment of emergency large vessel occlusions (ELVO) have led to a transformation in the delivery of stroke care. Because of the importance of time to treatment with endovascular thrombectomy (EVT), there has been renewed emphasis on improving stroke systems of care. In south Florida, there has been a proliferation of stroke centers over the past decade claiming to offer EVT due to the practice of self-attestation by the Agency for Healthcare Administration (AHCA). Concurrently, there are over a dozen EMS agencies in the region, leading to variability in pre-hospital protocols. Methods: To address the fragmented stroke landscape, in 2015 local EMS Medical Directors along with NeuroInterventionalists (NI) developed the South Florida Stroke Coalition (SFSC), and collaborated with the University of Miami Florida Stroke Registry (UM FSR) team. The core tenets were to: 1) Develop pre-hospital EMS stroke protocols; 2) Optimize in-hospital stroke processes to reduce times to treatment for ELVO; 3) Encourage all tri-county stroke centers to submit data to AHA/ASA Get with the Guidelines-Stroke (GWTG-S) program and participate in the UM FSR; 4) Develop a sustainable data transparency model for CSCs to allow EMS Medical Directors to understand quality of stroke care in their region; 5) Eliminate the practice of AHCA self-attestation of CSCs and require stroke centers to apply for Joint Commission certification. Results: The SFSC and the UM FSR analyzed AHCA criteria for Comprehensive Stroke Center (CSC) designation and compared them to those of the Joint Commission to better understand limitations of self-attestation. A sustainable mechanism for local hospitals to share stroke data with the EMS Medical Directors in their catchment areas was created through a regional dashboard initiative (figure 1 ). The following key variables were selected by the SFSC to provide a better understanding of the quality of care: 1) treatment rates for tPA and EVT, 2) door-to-needle time for tPA, 3) door-to-puncture time for EVT, 4) outcomes at 90 days using modified Rankin scale. Conclusion: To our knowledge, the Florida Stroke Registry Regional Dashboards developed as a grassroots effort between the SFSC and the UM FSR represents the first-of-its-kind, EMS-driven effort to improve stroke systems of care in a region that is comprised of a multitude of EMS agencies and numerous ELVO triage destinations within short distance of each other. Taken together, this data transparency initiative will be instrumental for EMS Medical Directors in future triage decision-making. Disclosures: B. Mehta: None. P. Antevy: None. R. Katz: None. J. Sessa: None. K. Scheppke: None. P. Pepe: None. R. Hanel: None. M. Mokin: None. C. Gutierrez: None. J. Romano: None. R. Nogueira: None. A. Jadhav: None. T. Leslie-Mazwi: None. R. Sacco: None.